STRATEGI PENGEMBANGAN EKOWISATA MANGROVE DI DESA BUWUN MAS KECAMATAN SEKOTONG KABUPATEN LOMBOK BARAT - Sopian Wildani; Lalu Yulendra; ander sriwi (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
Mangrove ecotourism in Buwun Mas Village is a tourist area that relies on mangroves as the main destinations, this tour has been inaugurated in 2022. This mangrove forest is the only tourist attraction in Buwun Mas Village which has been inaugurated as a tourist destination located in Jerangkang Village. This study aims to identify the potential and strategies for developing mangrove forest areas in Buwun Mas Village. This study uses a qualitative approach whose results are presented descriptively. The data was collected by means of observation, interview, and documentation techniques. The data analysis used was SWOT analysis with data collection steps, namely data reduction, data display, and data conclusions. The results showed that the development of the mangrove forest area into an ecotourism destination in Buwun Mas Village there were several driving and inhibiting factors, namely internal and external.